Consensus-Based Pricing Model for Professional Services: A Legal and Technological Approach in Indonesia - Nanin Koeswidi Astuti (International Journal of Business, Law, and Education, 2026)
The digital economy has significantly expanded professional service transactions in Indonesia; however, no established mechanism currently provides a reliable benchmark for determining fair service fees. This gap has contributed to price disparities, information asymmetry, and unequal bargaining power between service providers and clients. This study aims to examine the legal framework governing professional service pricing, assess the compatibility of a consensus-based pricing model with competition law principles, and develop a conceptual Consensus-Based Pricing Model. The study employs normative legal research using statutory, conceptual, and comparative approaches. The findings demonstrate that the proposed model does not constitute price fixing, as it merely provides a transparent, non-binding, and informative pricing benchmark while preserving the parties' freedom to negotiate the final price. By leveraging digital platforms through a co-regulatory approach, the model has the potential to reduce information asymmetry, strengthen consumer protection and legal certainty, and promote fair market competition.